2009
DOI: 10.1007/s00228-009-0650-7
|View full text |Cite
|
Sign up to set email alerts
|

The change in plasma GABA, glutamine and glutamate levels in fluoxetine- or S-citalopram-treated female patients with major depression

Abstract: Our findings may suggest that GABA, glutamate and glutamine play a role in depression and that plasma GABA may be used as a biomarker for treatment control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(80 citation statements)
references
References 41 publications
7
69
0
4
Order By: Relevance
“…Still, repeated maternal separation or stress altered or lead to overactivation of glutamate receptors in the brains of rats [36,37]. In humans with major depressive disorder, an increase in glutamate levels in the plasma and postmortem samples of the frontal cortex was also reported [38,39]. Such changes can lead to alterations in neurons, including excitotoxicity.…”
Section: Discussionmentioning
confidence: 89%
“…Still, repeated maternal separation or stress altered or lead to overactivation of glutamate receptors in the brains of rats [36,37]. In humans with major depressive disorder, an increase in glutamate levels in the plasma and postmortem samples of the frontal cortex was also reported [38,39]. Such changes can lead to alterations in neurons, including excitotoxicity.…”
Section: Discussionmentioning
confidence: 89%
“…The results of the present study indicated that both DA and HVA concentrations did not vary significantly between the normal and the CUMS model groups, and that fluoxetine showed no significant effect on either concentration. One possible reason was that the DA dysfunction in depression patients might be the sign of diathetic depression or depression subtypes, and medication could not change the concentration of DA or HVA [33].…”
Section: Methods Applicationmentioning
confidence: 99%
“…Los resultados mostraron que las concentraciones sanguíneas de GABA eran menores en las mujeres deprimidas que en las controles. En las mujeres bajo tratamiento, se observó que las concentraciones plasmáticas de GABA se incrementaron con respecto a las basales 47 .…”
Section: Estudios Clínicos: Trastorno Depresivo Mayor Y áCido Gamma-aunclassified